WCSMO-1 : proceedings of the First World Congress of Structural and Multidisciplinary Optimization, 28 May - 2 June 1995, Goslar, Germany - World Congress of Structural and Multidisciplinary Optimization (1st : 1995 : Goslar, Germany); Olhoff, Niels; Rozvany, George I. N.; International Society for Structural and Multidisciplinary Optimization (Oxford : Elsevier, 1995)
09